A new GTSeq resource to facilitate multijurisdictional research and management of walleye Sander vitreus. Issue 12 (14th December 2022) - Euclide, Peter T.; Larson, Wesley A.; Bootsma, Matthew; Miller, Loren M.; Scribner, Kim T.; Stott, Wendylee; Wilson, Chris C.; Latch, Emily K.
Abstract: Conservation and management professionals often work across jurisdictional boundaries to identify broad ecological patterns. These collaborations help to protect populations whose distributions span political borders. One common limitation to multijurisdictional collaboration is consistency in data recording and reporting. This limitation can impact genetic research, which relies on data about specific markers in an organism's genome. Incomplete overlap of markers between separate studies can prevent direct comparisons of results. Standardized marker panels can reduce the impact of this issue and provide a common starting place for new research. Genotyping‐in‐thousands (GTSeq) is one approach used to create standardized marker panels for nonmodel organisms. Here, we describe the development, optimization, and early assessments of a new GTSeq panel for use with walleye ( Sander vitreus ) from the Great Lakes region of North America. High genome‐coverage sequencing conducted using RAD capture provided genotypes for thousands of single nucleotide polymorphisms (SNPs). From these markers, SNP and microhaplotype markers were chosen, which were informative for genetic stock identification (GSI) and kinship analysis. The final GTSeq panel contained 500 markers, including 197 microhaplotypes and 303 SNPs. Leave‐one‐out GSI simulations indicated that GSI accuracy should be greater than 80% in most jurisdictions. The false‐positive rates of parent‐offspring and full‐sibling kinship identification were found to be low. Finally, genotypes could be consistently scored among separate sequencing runs >94% of the time. Results indicate that the GTSeq panel that we developed should perform well for multijurisdictional walleye research throughout the Great Lakes region. Abstract : New genetic marker panels are an important resource for wildlife management and conservation. Here, we develop and test a new GTSeq marker panel for walleye with Laurentian Great Lakes ancestry. The new panel provides accurate genetic stock and pedigree assignment for a large number of populations that will facilitate interjurisdictional research and collaboration.